2009
DOI: 10.1007/s10856-009-3810-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of hydroxyapatite/polycaprolactone–chitosan composites

Abstract: Hydroxyapatite (HA)/polycaprolactone (PCL)-chitosan (CS) composites were prepared by melt-blending. For the composites, the amount of HA was varied from 0% to 30% by weight. The morphology, structure and component of the composites were evaluated using environmental scanning electron microscope, X-ray diffraction and Fourier transform infrared spectroscope. The tensile properties were evaluated by tensile test. The bioactivity and degradation property were investigated after immersing in simulated body fluid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 29 publications
5
24
0
2
Order By: Relevance
“…At the same time, a lower heat of fusion (Δ H m ) and nearly similar X c were also observed. These results suggest that HANP can also change the crystallinity of the polymer and may accelerate the nucleation of the PCL segments [3033]. …”
Section: Resultsmentioning
confidence: 99%
“…At the same time, a lower heat of fusion (Δ H m ) and nearly similar X c were also observed. These results suggest that HANP can also change the crystallinity of the polymer and may accelerate the nucleation of the PCL segments [3033]. …”
Section: Resultsmentioning
confidence: 99%
“…But the problem of using such natural materials is their inferiority in mechanical properties [20]. Therefore, many studies have been reported on combination HA with biodegradable synthetic materials, such as poly (lactic acid) [21], poly (ε-caprolactone) (PCL) [22][24], poly (lactic-co-glycolic acid) [20], Poly (D,L-lactide) [25], to circumvent the drawbacks of natural polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, tricomponent systems with improved properties are becoming more popular as compared with chitosan (mono‐) and Chi‐HAp (bi‐component) scaffolds. Various components have been combined with Chi‐HAp to form effective tricomponent systems for tissue engineering, for example, collagen, gelatin, carbon nanotube, polycaprolactone, carboxymethyl cellulose, montmorillonite, and so forth 14–19. Among all the composite materials, collagens are becoming more suitable choice, as it promotes the structural and physiological functions more effectively.…”
Section: Introductionmentioning
confidence: 99%